2022
DOI: 10.1155/2022/1665021
|View full text |Cite|
|
Sign up to set email alerts
|

Neural Network Model for Perceptual Evaluation of Product Modelling Design Based on Multimodal Image Recognition

Abstract: With the homogenization of product function and performance, the design technology for product appearance quality has been increasingly valued by academia and industry and has become an effective technical way to meet the continuously growing diversified and personalized needs of consumers. The appearance quality attribute of a product can be characterized or described by its appearance image. Data-driven product appearance image design is based on the quantitative data of product appearance and consumer emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Convolution neural network is a kind of feedforward neural network with deep structure and convolution calculation and is one of the representative algorithms of deep learning [10][11][12]. Convolution neural network has the ability of representation learning and can translate and classify input information according to its hierarchical structure, so it is also called translation invariant artificial neural network.…”
Section: Relevant Technologies Of Image Detection and Recognitionmentioning
confidence: 99%
“…Convolution neural network is a kind of feedforward neural network with deep structure and convolution calculation and is one of the representative algorithms of deep learning [10][11][12]. Convolution neural network has the ability of representation learning and can translate and classify input information according to its hierarchical structure, so it is also called translation invariant artificial neural network.…”
Section: Relevant Technologies Of Image Detection and Recognitionmentioning
confidence: 99%
“…The above studies all start from the one-way mapping relationship between imagery and product modeling, but in fact, the mapping relationship between imagery and product modeling is complex, multi-directional, and non-linear [22]. Yang et al [23] and Wu and Jia [24] have studied the matching of the correspondence between multi-directional emotional imagery and stylistic features and established a non-linear model of the relationship between multi-directional imagery and stylistic design. Ding et al [25] and Zeng et al [26] used multiple regression analysis to establish a product modeling design prediction model reflecting imagery.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%